Application of Graphene and Its Derivatives in Environmental Management - Chen, Shutong (International Journal of Materials Science and Technology Studies, 2024)
Graphene, a novel nanomaterial, has demonstrated promising applications in environmental management due to its unique physicochemical properties. This paper reviews the practical applications of graphene in water treatment, air purification and waste management. In water treatment. graphene oxide has shown high efficiency in removing heavy metal ions and organic pollutants. In air purification, graphene-based catalysts exhibit excellent removal efficiency for nitrogen oxides and sulfur dioxide, while graphene oxide also performs exceptionally well in removing volatile organic compounds. Additionally, graphene's applications in waste management, including electrochemical waste treatment and thermal conductivity in waste incineration, highlight its potential in improving treatment efficiency and reducing harmful gas emissions. Despite the promising outlook for graphene in environmental improvement, challenges such as high production costs and long-term stability issues need further investigation. Future research should focus on reducing production costs, enhancing material performance, and assessing environmental impacts to facilitate the widespread application of graphene in environmental protection.